Hierarki Pengaruh Dalam Pemberitaan Gerakan Ekstra-Parlementer Agustus 2025 Di Inews TV - Sherly Violeta Fitri; Arif Alamsyah Siregar; M. Pradikto Satria Ramadhan; Adilla Aulia Ardin (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze the application of the Hierarchy of Influence in the news coverage of the August 2025 Extra-Parliamentary Movement on iNews TV, as well as to examine the news production process. Grounded in the Hierarchy of Influence theory proposed by Shoemaker and Reese, this research explores five levels of influence individual, media routines, organizational, extramedia, and ideological, within television news production. The study employs a qualitative approach using a constructivist paradigm. Data were collected through documentation analysis of iNews TV news broadcasts related to the movement, supported by literature review and complementary interviews. The findings indicate that news coverage is shaped by interactions among journalistic professionalism, editorial routines, organizational policies, and external contextual factors. At the individual and media routine levels, time constraints and news values influence story selection and presentation. At the organizational and extramedia levels, editorial considerations and reliance on official sources contribute to the prioritization of narratives emphasizing public order and stability. Ideological influences further frame the movement within broader national and social discourses. Overall, the study demonstrates that news content is constructed through layered influences rather than produced in a neutral manner. This research contributes to mass communication and media sociology by providing empirical insights into how national television media frame political events and social movements in contemporary Indonesia.